Social-emotional learning implementation and its impact on student achievement - Risa Ginting; Asep Herry Hernawan (Inovasi Kurikulum)
This article investigates social-emotional learning implementation in various educational institutions and its relation to student's academic and non-academic achievements. Social-emotional skills are essential as they have long-term impacts that can be felt in multiple aspects of life. The method used is a systematic literature review conducted by collecting, evaluating, and synthesizing various literature related to the research topic. The variables studied include methods for developing social-emotional competencies, implementing social-emotional learning, and its relation to students' academic and non-academic achievements. Data were obtained from literature searches on findings related to social-emotional competencies conducted over the past five years. The research findings indicate that social-emotional learning is applied using various methods and approaches across different levels of educational institutions. It was also found that social-emotional learning positively influences students' academic and non-academic achievements. Students with good social-emotional skills generally have better academic scores compared to their peers who do not possess such skills. They also feel happier, have better mental health, have higher attendance rates in class, and are rarely involved in problems with their peers.